2021
DOI: 10.1186/s13075-021-02581-0
|View full text |Cite
|
Sign up to set email alerts
|

Higher levels of anti-phosphorylcholine autoantibodies in early rheumatoid arthritis indicate lower risk of incident cardiovascular events

Abstract: Background The increased risk of cardiovascular events (CVE) in rheumatoid arthritis (RA) is not fully explained by traditional risk factors. Immuno-inflammatory mechanisms and autoantibodies could be involved in the pathogenesis of atherosclerotic disease. It has been suggested that anti-phosphorylcholine antibodies (anti-PC) of the IgM subclass may have atheroprotective effects. Here, we aimed to investigate the association between levels of IgM anti-PC antibodies with CVE in patients with ea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 46 publications
(71 reference statements)
0
1
0
Order By: Relevance
“… 62 It has been reported that the lower titers of anti-phosphorylcholine antibodies in individuals with RA and SLE were probably associated with an increased risk of cardiovascular events. 63 , 64 Hence, the capacity to produce anti-phosphorylcholine antibodies might be related to the development of atherosclerosis.…”
Section: Discussionmentioning
confidence: 99%
“… 62 It has been reported that the lower titers of anti-phosphorylcholine antibodies in individuals with RA and SLE were probably associated with an increased risk of cardiovascular events. 63 , 64 Hence, the capacity to produce anti-phosphorylcholine antibodies might be related to the development of atherosclerosis.…”
Section: Discussionmentioning
confidence: 99%